Théâtre et enfermement : la création collective comme modalité de l’expérience d’enquête en prison - Chloé Branders (Criminocorpus)
This paper describes an original research posture which, by mixing the object with the method, assures to the researcher a double position of actress and observer, both on the field and on stage. Indeed, to study the processes of collective theatrical creation in the particular context of confinement, participant observation was chosen as a methodology for data collection. In this article, after presenting the grounds and defining the contours of the object of study, we will explain how collective theatrical creation is articulated to the experience of the investigation in a closed institution. Particular attention will be given to reflexivity, which, mobilized as a function of lucidity in research, lead to analyze the strong involvement of the researcher in his field. Finally, in order to link the inductive process and the creative process, the conceptualization of the peril developed by Riccardo Cappi will be mobilized. Exhausting its main characteristics, the major stages of ethnographic research will be revisited to explain how the researcher experienced the collective theatrical creation in the specific context of prison.